2021
DOI: 10.1177/10556656211007000
|View full text |Cite
|
Sign up to set email alerts
|

The Palatal Fistula Closure Using Buccal Fat Graft After Palatoplasty for Cleft Palate: Two Case Reports

Abstract: Fistula recurrence is high after secondary follow-up operation to close the fistula after primary palatal surgery. Therefore, preventing fistula recurrence is important. Here, we describe the technique of closing palatal fistula after palatal surgery with a buccal fat graft in 2 cases. We elevate the mucosal flap around the palatal fistula, suture the nasal mucosa, transplant the buccal fat between the nasal and oral mucosa for the palatal fistula after palatal surgery, and suture the oral mucosa. Palatal fist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…40 The volume of the transposable fat pad can vary considerably, and it must be handled very carefully at all times. 40 A detailed description of the anatomy and physiology of the buccal fat pad can be found in the literature. 8,9 There has been an increase in interest in the use of the buccal fat pad in oral reconstruction as evidenced by many case reports and case series available on the subject.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…40 The volume of the transposable fat pad can vary considerably, and it must be handled very carefully at all times. 40 A detailed description of the anatomy and physiology of the buccal fat pad can be found in the literature. 8,9 There has been an increase in interest in the use of the buccal fat pad in oral reconstruction as evidenced by many case reports and case series available on the subject.…”
Section: Discussionmentioning
confidence: 99%
“…The fat pad, by virtue of its physiologic composition, also provides a hydrophobic middle layer between the palatal mucosal flap and the bone graft. 40 The considerable number of reports on the use of buccal fat pad in oral reconstruction attest to its usefulness and increased acceptance by clinicians. 20,58 The results of this study show that in the repair of the cleft palate, the BFP has found usefulness in areas such as primary and secondary repair of the cleft palate, obturation of lateral palatal mucoperiosteal defect in the bipedicled flap technique, adjunct for soft tissue coverage in alveolar cleft repair among others.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The buccal fat pad flap is reported to be a reliable and effective flap with clinical application in reconstruction of oral defects due to its high vascularity, reducing tissue hypoxia and improving graft survival. This has been used to treat oroantral fistula, congenital defects such as the cleft palate, osteonecrosis of the jawbone and defects induced by removal of tumours or cysts ( Egyedi, 1977 ; Ashtiani et al, 2011 ; Kim et al, 2017 ; Yaguchi et al, 2021 ).…”
Section: Exporting the Properties Of Oral Epithelia – The Source For Future Therapies In Wound Repair?mentioning
confidence: 99%